2008
DOI: 10.4049/jimmunol.180.5.2839
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate and Heparin Enhance ERK Phosphorylation and Mediate preBCR-Dependent Events during B Lymphopoiesis

Abstract: As B lineage cells develop, they interact with cells, proteins, and extracellular matrix components of the surrounding microenvironment. In vitro, one critical checkpoint for developing cells occurs as they lose responsiveness to IL-7. These cells require contact with either stromal cells or other B lineage cells to mature. Our results demonstrate that heparan sulfate and heparin are able to promote this transition when added exogenously to the culture system or when heparan sulfate-bearing cell lines are cocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Pre-BCR and IL-7R-mediated signals are indispensable for B-cell development in BM. 28,29 Notably, several studies have shown that HS can interact with both the pre-BCR 30,31 and with IL-7, 32 suggesting that they may play a role in controlling early B lymphopoiesis. However, the critical HSs in these in vitro studies were either exogenously added or expressed by supporting stromal cells, rather than by the B cells, the Glce-deficient cells in our current model.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-BCR and IL-7R-mediated signals are indispensable for B-cell development in BM. 28,29 Notably, several studies have shown that HS can interact with both the pre-BCR 30,31 and with IL-7, 32 suggesting that they may play a role in controlling early B lymphopoiesis. However, the critical HSs in these in vitro studies were either exogenously added or expressed by supporting stromal cells, rather than by the B cells, the Glce-deficient cells in our current model.…”
Section: Discussionmentioning
confidence: 99%
“…7). In support of this idea, heparan sulfate and galectin-1 appear to enhance the phosphorylation of signaling molecules downstream of the pre-BCR, such as Ig␣ and ERK (28,51,52). All of these models are not mutually exclusive, and ligand-mediated enhancement of autonomous pre-BCR signals may have evolved to maintain those pre-B cells that express only low amounts of the pre-BCR at their cell surface.…”
Section: Discussionmentioning
confidence: 93%
“…These tails are not required for SLC assembly [21,22], but protrude from the pre-BCR at a position where the antigen binding site would be located in the BCR [16,19]; thus the tails are accessible for binding of self-antigens. Indeed, we and others demonstrated that the l5 non-Ig-like tail is an autoreactive entity and can interact with bone marrow stroma cell-associated self-antigens, such as heparan sulfate and galectin-1, both of which enhance pre-BCR signals (Box 3) [17,22,23]. In addition, the l5 tail renders the pre-BCR reactive against itself, thereby leading to pre-BCR self-oligomerization and signal initiation [16,24].…”
Section: Opinionmentioning
confidence: 95%
“…Therefore, the incomplete nature of the antigen binding site in a pre-BCR makes positive selection by foreign antigens an inappropriate driving force for the proliferation of pre-B cells. Indeed, pre-BCR-mediated proliferation of pre-B cells, in contrast to BCR-mediated proliferation of mature B cells, can occur independently of foreign antigens [10,11,17].…”
Section: Opinionmentioning
confidence: 95%